The new Brazilian bankruptcy law and its impacts on the credit market - Ferreira, Rafael de Vasconcelos Xavier (2010)
In early 2005 a new bankruptcy law was approved by the Brazilian Congress, taking effect a few months later. The new legislation improved creditor protection and the bankruptcy system’s efficiency. This paper tries to shed some light on the empirical consequences of a bankruptcy reform on a poorly developed credit market. Using data from Argentine, Brazilian, Chilean and Mexican firms, we estimated two diff-in-diff models with differential trends: one with a firm-specific trend and the other with a country-specific macro trend. Both models yielded similar results. We found significant impacts on the supply of credit, the cost of debt, and the supply of secured, unsecured and long-term debt. No significant impacts were found for the level of short-term debt.